Plantar keloids: diagnostic and therapeutic issues in six patients. (4th August 2014) - Vanhaecke, C.; Hickman, G.; Cavelier‐Balloy, B.; Masson, V.; Duron, J.‐B.; Gorj, M.; May, P.; Schneider, P.; Vilmer, C.; Bagot, M.; Battistella, M.; Petit, A.
Abstract Background Keloids are benign fibro‐proliferative skin lesions that very rarely occur on the soles. Because of their rarity, the diagnosis of plantar keloids can be difficult. We describe the clinical and histopathological characteristics of eight plantar keloids. Methods All patients presenting with plantar keloids between 2005 and 2012 in our Dermatology unit were retrospectively included. Diagnosis was definitely established by re‐reading of pathological slides in all cases. Clinical characteristics, histopathological features, treatments given and their results were collected. Results Six patients were included. Five patients had a single plantar keloid and one had three lesions. They all were of African descent. Only one patient remembered of a previous injury at the site of the keloid. Three patients presented with associated extra‐plantar keloids. In four patients, the diagnosis of keloid was not initially suspected clinically or histologically. Re‐reading of the clinical photographs showed that the eight plantar keloids shared common morphological features, leading to a distinctive clinical picture, defined by a hardened lesion of rounded or polycyclic shape, with a pink surface crossed by keratotic furrows and the presence of a hyperkeratotic rim. Concerning pathological features, typical hyalinized collagen can be missing and deep fibrosis should not rule out the diagnosis of keloid. Intralesional injection of triamcinolone acetonide and orthopaedic shoes were useful. All patients who had surgical excision presented recurrence. Conclusion The knowledge of the clinical features of plantar keloids is helpful to the diagnosis. There is no well‐established treatment, but supportive measures are important.